Sex and rural-urban differences in the prevalence of childhood visual impairment in Taiwan: A nationwide population-based study. (August 2020) - Lai, Der-Chung; Tseng, Yen-Cheng; Guo, How-Ran
Abstract: Background: Visual impairment (VI) is a major developmental disability in children, but data at the national level are limited. Aims: We conducted a nationwide study in Taiwan to assess the sex and rural-urban differences in VI. Methods and procedures: Using data from the national disability registry, we calculated prevalence rates by age, sex, and geographic area and assessed changes from 2004 to 2010. We excluded cases under 3 years old because the government discourages certification at this age. Outcomes and results: Between 2004 and 2010, the overall prevalence rate fluctuated between 3.48/10, 000 and 3.66/10, 000. Boys had higher prevalence rates in all years, and the boy-to-girl prevalence rate ratios ranged from 1.24 to 1.30 ( p < 0.05 in all years), without an apparent time trend. The rates generally decreased over time in rural areas ( p= 0.008), but increased in urban areas ( p= 0.029); this resulted in a decreasing time trend ( p = 0.001) in the rural-to-urban prevalence rate ratios (1.32 to 1.09; p < 0.05 except for 2010). Conclusions and implications: Boys are more likely to experience VI in Taiwan. Rural areas had higher prevalence rates than urban areas, but the difference has been decreasing over time. Identifying factors underlying this reduction may help the prevention of VI.